Karakteristik Anak Berkebutuhan Khusus di Sekolah Dasar Negeri (Inklusi) di Kota Palangka Raya: Children Characteristics of Special Needs in Primary School (Inclusion) in Palangka Raya - Riadin, Agung; Misyanto, Misyanto; Usop, Dwi Sari (Anterior Jurnal, 2017)
Parents of children with special needs want their children to attend public schools, together with other children. The desire is supported by the government by launching an inclusive school. This study aims 1). Knowing the characteristics of children with special needs in Elementary School (Inclusion) in Palangkaraya City, 2). Knowing the impact of the presence of children with special needs in Elementary School (Inclusion) in Palangka Raya city, 3). Knowing the abilities of children with special needs in Elementary School (Inclusion) in Palangka Raya city. The research approach used is the qualitative approach. Methods of data collection using interviews, observation, and documentation. The results of this study indicate that the characteristics of children with special needs individually vary. However, its main characteristics, namely experiencing weakness in the academic field. On the other hand, children with special needs in Palangka Raya City Inclusion School have more advantages in the non-academic field.